The microstructure and corrosion characteristic of Al-10 wt%RE (Re= Ce, Nd, La, Y) binary aluminum alloys in natural seawater - Rui Xie; Quantong Jiang; Chang Liu; Xinhe Wu; Yahui Geng; Jizhou Duan; Baorong Hou (Journal of Materials Research and Technology)
This study presented a thorough investigation into the microstructure, precipitated phases, and corrosion resistance of Al-10 wt%Ce, Al-10 wt%Nd, Al-10 wt%La, and Al-10 wt%Y binary alloys when exposed to natural seawater. The microstructural analysis, conducted using optical microscopy, scanning electron microscopy (SEM), X-ray diffraction (XRD), and transmission electron microscopy (TEM), revealed the presence of distinct precipitated phases. The distinct precipitated phases Al3Ce, Al3Nd, Al11La3, and Al3Y, respectively, have different morphologies and are expected to influence the corrosion resistance. The corrosion behavior of these alloys was evaluated through natural seawater immersion tests and electrochemical experiments, which demonstrated varying degrees of corrosion resistance. The average corrosion mass loss rates and average corrosion depths of the alloys in natural seawater were found to follow the order: Al–Y < Al–Ce < Al–La < Al–Nd. Theoretical explanations for the experimental outcomes were provided by analyzing the different types of precipitates, the electronic structures, and the crystallographic structures of the rare earth elements involved. This research contributes valuable theoretical and empirical data, supporting the application of rare earth aluminum alloys in structural materials for marine equipment.